2022
DOI: 10.5582/bst.2022.01281
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stellate cell exosome-derived circWDR25 promotes the progression of hepatocellular carcinoma <i>via</i> the miRNA-4474-3P-ALOX-15 and EMT axes

Abstract: Keywordsliver cancer, mesenchymal cells, extracellular vesicles, circular RNA, prognosisRecently, the emerging role of circular RNAs (circRNAs) in tumor development and progression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…[45][46][47] circRNAs can also affect the apoptosis of cancer cells and thus affect the programmed cell death of HCC, 48,49 or influence HCC invasion and metastasis by affecting the epithelial-to-mesenchymal transition (EMT). 50,51 Here, in vitro and in vivo experiments manifested that circSLC39A5 inhibited the proliferation, migration, and invasion of HCC cells, promoted cells apoptosis, and was associated with low expression of proliferation index Ki67 and capillarity marker CD34. Notably, it has been reported that CD34 + endothelium-coated tumor clusters can be released into the bloodstream to accelerate extrahepatic metastasis via an EMTindependent pathway.…”
Section: Discussionmentioning
confidence: 92%
“…[45][46][47] circRNAs can also affect the apoptosis of cancer cells and thus affect the programmed cell death of HCC, 48,49 or influence HCC invasion and metastasis by affecting the epithelial-to-mesenchymal transition (EMT). 50,51 Here, in vitro and in vivo experiments manifested that circSLC39A5 inhibited the proliferation, migration, and invasion of HCC cells, promoted cells apoptosis, and was associated with low expression of proliferation index Ki67 and capillarity marker CD34. Notably, it has been reported that CD34 + endothelium-coated tumor clusters can be released into the bloodstream to accelerate extrahepatic metastasis via an EMTindependent pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Exosomes have been implicated in physiological and pathological processes, such as angiogenesis [ 18 ], immune responses [ 23 ], homeostasis maintenance [ 24 ], coagulation [ 25 ], inflammation [ 26 ], cancer progression [ 27 ], and antigen presentation [ 28 ]. Nucleic acids, proteins, and metabolites delivered by exosomes into recipient cells effectively alter their biological response [ 12 ].…”
Section: Exosomes: a Means Of Intercellular Communicationmentioning
confidence: 99%
“…CircRNA was once considered as the noise of transcription but has attracted increasing attention in recent years. The results of several research teams have identified many important roles of multiple circRNAs in HCC [ 18 , 23 , 27 ].…”
Section: Circrna: An Important Regulatory Factor In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that during the progression of many types of cancer such as lung, bladder, and liver cancer, tumor-associated sEVs carry and release a variety of active components such as miRNAs, proteins, and circRNAs into the surrounding cells. This further promotes the metastasis of tumor cells by causing EMT of the recipient cells through various pathways [ 24 , 48 , 49 ]. In addition, sEVs affect the EMT of recipient cells and play an important role in CRC metastasis ( Table 2 ).…”
Section: Small Extracellular Vesicles Mediate Epithelial Mesenchymal ...mentioning
confidence: 99%